A Serious Game for Improving Reading Skill of Preschoolers - Muhammad Rizki Nugraha; Yusep Rosmansyah; Evi Dewi Sri Mulyani; Teuku Mufizar; Dede Syahrul Anwar; Cepi Rahmat Hidayat (Elinvo (Electronics, Informatics, and Vocational Education), 2022)
Nowadays, many games are made for educational or learning purposes. However, the unresolved challenge remains, and the perfect balance between the fun and learning aspects remains. This paper represents an effort toward such a challenge by way of game difficulty dynamization implementation in a game to improve preschoolers reading skills using Dynamic Difficulty Adjustment dan Procedural Content Generation. To measure the balance of fun and learning aspects in the game, experiments were conducted involving 32 preschoolers. The proposed game can generate 10.962 game content in various difficulties and balance the fun and learning aspects according to the enjoyment factor's average value. Students could enjoy the game while significantly gaining an increase in the average reading skill, based on the t-test value and NGain value of 0.551.